Rapid acceleration of ice-cover loss from Northern Hemisphere lakes above critical air temperature thresholds - Jian Zhou; Weijia Wang; Yaru Ma; Linwang Yuan; Changchun Huang; Kun Shi; Peter R. Leavitt (Proceedings of the National Academy of Sciences, 2026)
Widespread declines in lake-ice cover are a hallmark of climate warming, yet the dynamic sensitivity of ice cover to thermal forcing remains poorly understood across broad climatic gradients. By analyzing an extensive dataset from 724 Northern Hemisphere lakes between 2000 and 2022, we quantify the responsiveness of lake-ice phenology to changes in air temperature and project their future trajectories. Our hemispheric analysis reveals a pronounced asymmetrical sensitivity where ice-decay processes are significantly more responsive to warming than ice-formation events. We identify critical thermal threshold of mean winter air temperature (AT) ranging from −13.7 to −6.8 °C, beyond which phenological sensitivity accelerates nonlinearly. Once these winter temperature breakpoints are surpassed, the sensitivity of ice loss increases by up to 22-fold, signaling a threshold-dependent collapse of the seasonal ice cycle. These threshold-dependent responses are primarily driven by broad-scale thermal and radiative regimes, particularly winter AT and surface albedo, rather than localized lake morphology. Future projections indicate that under high-emission scenarios, ice-cover duration will contract by approximately 40 d, and the proportion of lakes crossing critical thermal thresholds and entering a state of accelerated phenological sensitivity is expected to rise from 23 to 70% by the end of the century. These findings suggest that many temperate and southern boreal lakes are nearing a state of heightened vulnerability where marginal warming will trigger abrupt and potentially irreversible ecological shifts.